Epidemiology and outcomes of ventilator-associated events in critically ill children: Evaluation of three different definitions. (4th February 2023) - Papakyritsi, Dimitra; Iosifidis, Elias; Kalamitsou, Serafia; Chorafa, Elisavet; Volakli, Eleni; Peña-López, Yolanda; Sdougka, Maria; Roilides, Emmanuel
Abstract: Objective: Ventilator-associated pneumonia (VAP) is one of the most common healthcare-associated infections in pediatric intensive care units (PICUs), but its definite diagnosis remains controversial. The CDC Ventilator-Associated Event (VAE) module (validated in adults) constitutes a new approach for VAP surveillance. Design: We described epidemiological characteristics of PICU VAE cases, investigated possible risk factors, and evaluated 3 different sets of diagnostic VAE criteria. Setting: This study was conducted in a PICU in a tertiary-care general hospital in northern Greece during 2017–2019. Patients: The study included patients aged 35 days–16 years who received mechanical ventilation. Methods: From medical records, we retrieved epidemiological data, clinical data, and laboratory characteristics as well as ventilator settings for our analysis. We assessed "oxygen deterioration" for the tier 1 CDC VAE module using 3 sets of diagnostic criteria: (1) CDC adult VAE criteria [increase of daily minimum fraction of inspired oxygen (FiO2) ≥ 0.2 or positive end expiratory pressure (PEEP) ≥ 3 cmH2O for 2 days], (2) the US pediatric VAE criteria [increase of FiO2 ≥ 0.25 or mean airway pressure (MAP) ≥ 4 cmH2O for 2 days], and (3) the European pediatric VAE criteria (increase of FiO2 ≥ 0.2 or PEEP ≥ 2 cmH2O for 1 day or increase of FiO2 ≥ 0.15 and PEEP ≥ 1 cm H2O for 1 day). Results: Among 326 children admitted to the PICU, 301 received mechanical ventilation. The incidence rate according to the CDC adult VAE criteria was 4.7 per 1, 000 ventilator days. For the US pediatric VAE criteria the incidence rate was 6 per 1, 000 ventilator days. For the European pediatric VAE criteria the incidence rate was 9.7 per 1, 000 ventilator days. These results revealed statistically significant correlation of all 3 algorithms with adverse outcomes, including mortality. Conclusions: All VAE algorithms were associated with higher mortality rates. Our findings highlight the need for a unified pediatric VAE definition to improve preventive strategies.